2022
DOI: 10.1111/hex.13541
|View full text |Cite
|
Sign up to set email alerts
|

Exploring motivations and resistances for implementing shared decision‐making in clinical practice: A systematic review based on a structure–process–outcome model

Abstract: Objective: Shared decision-making (SDM) as a multicollaborative approach is vital for facilitating patient-centred care. Considering the limited clinical practice, we attempted to synthesize the motivations and resistances, and investigate their mutual relationships for advancing the implementation of SDM.Methods: A comprehensive systematic review using Preferred Reporting Items for Systematic Review and Meta-Analysis guidelines was performed. 'Shared decision making' was searched as the mesh term through PubM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…As there are evidenced benefits to person-centered care within the context of chronic condition self-management [30], we should take into account the persons' day-to-day experience, knowledge, and action over time in managing their health, to strengthen and improve a person's control over their health. Sharing knowledge and decision making is also vital for facilitating patient-centered care [31], and improves the relationship between patients and HCPs.…”
Section: Discussionmentioning
confidence: 99%
“…As there are evidenced benefits to person-centered care within the context of chronic condition self-management [30], we should take into account the persons' day-to-day experience, knowledge, and action over time in managing their health, to strengthen and improve a person's control over their health. Sharing knowledge and decision making is also vital for facilitating patient-centered care [31], and improves the relationship between patients and HCPs.…”
Section: Discussionmentioning
confidence: 99%
“…More implicit psychological parameters might influence the occurrence of SDM, and unless these are specified, one has to conclude that SDM can be performed with any patient. Another review found that trusting physicians increased the probability of engaging in SDM although unconditional trust should be regarded as negative as a collaborative relationship has to be established in SDM [ 153 ]. Also, patient characteristics like better physical health, higher self-efficacy, higher decision-making skills, younger age, and higher health literacy were associated with higher participation in SDM.…”
Section: Reviewmentioning
confidence: 99%
“…Ineffective SDM was characterized by a lack of humanistic concern. Organizational support, like the financial compensation of additional time, is needed for physicians to implement SDM [ 153 ]. Physicians were less supportive of SDM in situations where they thought that well-evidenced guidelines favored one treatment over another [ 154 ].…”
Section: Reviewmentioning
confidence: 99%
“…In the process of brownfield redevelopment, capital investment (e.g., environmental remediation and renovation construction costs), matching measures (e.g., regional planning, government policy support and supervision, and management), basic conditions of construction and renovation enterprises, and public opinion guidance (e.g., access to environmental information) significantly affect the process of brownfield redevelopment. Therefore, coordinating the relevant interests of all participants is the key to the success of the project 28 .…”
Section: Establishment Of Brownfield Redevelopment Evaluation Index S...mentioning
confidence: 99%